2016
DOI: 10.1016/j.ecoleng.2015.12.043
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bacterial communities in wetland mesocosms receiving pharmaceutical-enriched wastewater

Abstract: a b s t r a c tA 16S rRNA gene multiplex 454 pyrosequencing approach was used to characterize the structure of the bacterial community in subsurface flow constructed wetlands planted with Typha angustifolia and unplanted wetland mesocosms receiving ibuprofen-enriched wastewater at a concentration of 250 g L −1 . The removal efficiency of ibuprofen (IBP) in the planted beds (78.5%) was significantly higher than that in the unplanted beds (57.9%) (P ≤ 0.05). The presence of ibuprofen significantly (P ≤ 0.05) red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…It was found that Nitrospira and Firmicutes served as an important function in the treatment of wastewater with pharmaceuticals [21]. Similarly, Zhang et al [46] also found that Firmicutes, Actinobacteria and Proteobacteriain had the best adaptation to the changed external environment in wetland systems. Nitrospira, belonging to nitrite oxidizing bacteria (NOB), play a key role in the secondary step of nitrifying [52].…”
Section: Resultsmentioning
confidence: 99%
“…It was found that Nitrospira and Firmicutes served as an important function in the treatment of wastewater with pharmaceuticals [21]. Similarly, Zhang et al [46] also found that Firmicutes, Actinobacteria and Proteobacteriain had the best adaptation to the changed external environment in wetland systems. Nitrospira, belonging to nitrite oxidizing bacteria (NOB), play a key role in the secondary step of nitrifying [52].…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that biotic pathways (microbial and plant uptake) are the most probable degradation routes for some PhCs (e.g., References [32,34,42,62,72,89]). In addition to direct uptake, the indirect positive effects of plant presence such as degradation by enzymatic exudates, as well as release of oxygen and root exudates (such as carbohydrates and amino acids) by the plant roots in the rhizosphere, which can provide organic carbon and a nutrient source for microorganisms, supports them in aerobically degrading and consequently enhancing the overall bioavailability of PhCs (e.g., References [32,37,52,90,91]).…”
Section: Role Of Plantsmentioning
confidence: 99%
“…, Zhang et al. ). Changes in the diversity and taxonomic composition of stream biofilms may have important implications for the structure and function of these communities and the ecosystem services they provide.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, recent research illustrates that exposure to anthropogenic contaminants such as pharmaceuticals and personal care products (hereafter referred to as drugs) can influence stream biofilm function, for example, by suppressing processes such as primary production and respiration (Bunch and Bernot 2011, Rosi-Marshall et al 2013). In addition, continuous exposure to drugs can alter the diversity and taxonomic composition of microbial communities in freshwater ecosystems by selecting for organisms that can tolerate or in some cases digest the contaminant (Drury et al 2013a, Rosi-Marshall et al 2013, Zhang et al 2016. Changes in the diversity and taxonomic composition of stream biofilms may have important implications for the structure and function of these communities and the ecosystem services they provide.…”
Section: Introductionmentioning
confidence: 99%